The Alarming Resurgence of Dengue Fever with Unusual Clinical Manifestations and Deadly Consequences of 2023 Outbreak in Bangladesh - Islam, Quazi Tarikul; Tasnim, Refaya; Sagar, Hironmoy Barman; Noor, Nawsabah; Ahmed, Asif; Hasan, Taufiq (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: Dengue fever has become a significant concern in Bangladesh in recent years. The country is currently experiencing the most significant and deadliest outbreak in 2023. In this article, we will delve into the current dengue situation in Bangladesh, analyzing its clinical profile and grave consequences. Materials and methods: This multicentric cross-sectional study analyzed 499 confirmed dengue patients admitted between May 1, 2023, and September 30, 2023, in the Department of Medicine, Popular Medical College and Hospital, and Sir Salimullah Medical College and Mitford Hospital, Dhaka. Patients were categorized into dengue Groups A, B, and C. We tabulated and expressed categorical variables (gender, clinical manifestations, comorbidity, radiological and laboratory findings) as frequencies and percentages and explored relationships between demographics, clinical manifestations, and severity. The chisquare test compared proportions, with p d” 0.05 considered significant. Duration of illness and hospital stay were analyzed using the Mann-Whitney U test. Results: Among 499 patients, the 21-40 age group with a male predominance was most affected. Predominant symptoms were fever and gastrointestinal issues. Bleeding, myalgia, and rash were less common. Group C displayed a shift towards Dengue Shock Syndrome (DSS) rather than Dengue Hemorrhagic Fever (DHF), with 125 patients experiencing shock. Group B exhibited significant ultrasonographic findings, such as ascites, hepatomegaly, and splenomegaly, while Group C had more pronounced radiological findings of pleural effusion and pneumonia, predominantly unilateral right-sided pleural effusion. In both Groups B and C, liver transaminases, serum ferritin, and serum lipase were consistently elevated. Tragically, 9 (1.80%) patients, all in Group C, did not survive. Conclusions: In summary, our study on the current dengue outbreak in Bangladesh indicates a worrying shift to severe Dengue Shock Syndrome, more prevalent than hemorrhagic fever. Prominent gastrointestinal symptoms, less bleeding, and higher mortality in Group C emphasize the crisis. J Bangladesh Coll Phys Surg 2023; 41: 12-20